Estudio de prefactibilidad para la producción de helados de fresa (Fragaria) con leche en paletas y su distribución a través de máquinas dispensadoras en universidades de Lima Metropolitana - Castillo Barrenechea, Deborah Andrea (2022)
Implementing strawberry ice cream popsicles on vending machines contributes to healthy nutrition for students, teachers and non-teaching staff of universities due to the very limited time they have between breaks or free times between classes. Therefore, producing strawberry popsicles and distributing them through vending machines is a healthy and convenient alternative for people who attend university centers, as well as facilitating purchase and avoiding queues for their acquisition. The demand is segmented by the number of people who attend in a regular and summer cycle, resulting in 1 317 602 strawberry ice cream popsicles in the fifth year of the project, demand that has to be adapted to the market share that the project will have, being 20%, resulting in 263 520 strawberry ice cream popsicles with milk in the year 2027. The plant will be located in Lurin, in the city of Lima, and the location was determined taking into account the factors of land availability, land cost, public safety, and ease of operating procedures. The plant size is limited by the market size due to the value is above the break-even point and the other sizes do not represent a limiting factor in the production of ice cream popsicles. In the project engineering, the production process, the balance of materials, the production program, the technology to be used, and the machinery and operator requirements are detailed. The total area of the plant was calculated to be 852,6 m2. The production and price cost of the product will be S/ 5,60 and S/ 7,00, respectively. The economic and financial evaluation of the project showed that it is realizable since it has an NPV (Net Present Value) of S/.446 741,6, an IRR (Internal Rate of Return) higher than the COK and the payback period of the investment is in 2 years, these indicators belong to the financial cash flow and indicate that acquiring a loan is the best alternative for the investment.